Identifying the definite base of COI for extraction of DNA sequences using LPBS - Syed Abdullah, Sharifah Lailee; Harun, Hazaruddin; Mohd Hussin, Naimah; Hamid, Jiwa Noris; Mohamed Hanaphi, Roziana (2012)
This paper presents the use of the `Linear-PSO with Binary Search' (LPBS) algorithm for discovering motifs, especially species-specific motifs.In this study, two samples from different fragments of `mitochondrial cytochrome C oxidase subunit I' (COI/COX1) were collected from the Genbank online database.DNA sequences for the first sample are a mix of different fragments of COI and the second sample is from the same fragment of COI.The genome of COI was used as a reference set and other DNA sequences were used as a comparison set.All the collected DNA sequences are from the same species.The results show that the LPBS algorithm is able to discover motifs of greater length when using DNA sequences from the same fragment of COI.The experiment also found that 139 can be used as a starting base for COI DNA sequences extraction to discover species-specific motifs.